Manajemen Pendistribusian Zakat di YBM PLN Unit Wilayah Sumatera Utara - Isna Khairani; Muhammad Yafiz (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
In distributing zakat, zakat management is required which details the management of zakat given from an institution to prospective zakat recipients. Management of zakat distribution is carried out to make it easier for Amil to be directed in terms of zakat distribution in accordance with sharia principles. In this research the author tries to make research and analysis regarding the management of zakat distribution at the North Sumatra Regional Unit PLN Baitul Mall Foundation which includes planning, organizing, distributing zakat, as well as monitoring the validity of muzaki when receiving zakat, such as the validity of muzaki in terms of residence and family. , and education. The results of this research will show that the North Sumatra Regional Unit PLN Baitul Mall Foundation has become a superior ZIS (zakat, infaq, shadaqoh) management institution that is trustworthy, professional and transparent within PT PLN (Persero) in empowering mustahik to become muzaki.